Complexometric determination of mercury based on a selective masking reaction - Romero, Mercedes (2009)
In the first analytical chemistry course, students are introduced to the concepts of equilibrium in water solutions and classical (non-instrumental) analytical methods. Our teaching experience shows that "real samples" stimulate students' enthusiasm for the laboratory work. From this diagnostic, we implemented an optional activity at the end of the first analytical chemistry course. We suggested that the students propose a lab project that awakens their curiosity and perform it with the instructor's supervision. The project described here was one of the most interesting proposed experiments. The students' goal was to test the potential environmental leaching of mercury from common 12 V batteries that were improperly disposed, without following the specific environmental policies for this extremely harmful material. The battery labels did not specify the composition of electroactive ions. To simulate the disposal situation, the batteries were submerged in water for one month. The project consisted of an initial experimental design; a bibliographic search of classical methods for detection of the mercury ion; choice and optimization of the selected technique with standard solutions, pretreatment, and analysis of "real" samples; and conclusions. With these optional activities students are challenged to find a real-world problem and to solve a real analytical problem by thinking independently about a specific issue and searching literature about the proper analytical methods.